Chichibabin pyridinium synthesis via oxidative decarboxylation of photoexcited α-enamine acids. Issue 10 (8th January 2021) - Pan, Zhiqiang; Hu, Fengchi; Jiang, Di; Liu, Yuchang; Xia, Chengfeng
Abstract : The photoexcited enamines derived from α-amino acids could undergo an oxidative decarboxylation followed by a Chichibabin cyclization to afford highly substituted pyridiniums. Abstract : A visible light-induced decarboxylative Chichibabin pyridinium synthesis between α-amino acids and aldehydes was developed. When the in situ generated α-enamine acids were photoexcited, they were oxidized by aerobic oxygen to give radical cation species. After decarboxylation and further oxidation, the generated iminium undergoes Chichibabin cyclization to afford pyridiniums. This photochemical protocol enables the synthesis of various tetra-substituted pyridiniums and related natural products in one-step.